Knowledge, attitudes, and practices of Indonesian medical and non-medical undergraduate students toward COVID-19 - Thania Lathifatunnisa Putri Agusti; Nahwa Arkhaesi; Anugrah Riansari; Rebriarina Hapsari (International Journal of Public Health Science (IJPHS), 2022)
As the coronavirus disease 2019 (COVID-19) pandemic spread across Indonesia, good knowledge, proper attitude, and appropriate practices among undergraduate students must be achieved before starting a face-to-face lecture. These are also important since most students are active in social media and can spread true or false rumors regarding COVID-19. This study aimed to assess the level of knowledge, attitudes, and practices of medical and non-medical undergraduate students toward COVID-19. A 51-item online questionnaire was developed and sent to random undergraduate students from different faculties in Universitas Diponegoro, Indonesia. A total of 482 students completed the survey. The Chi-square test showed significant associations in the level of knowledge, attitudes, and practices towards the COVID-19 between medical and non-medical students, where medical students have better knowledge, attitudes, and practices than non-medical students. This study's findings may become the basis for an awareness campaign planning among students in particular and the public in general, which at this time most student activities are still carried out online and to prepare face-to-face lectures and also to deepen the material regarding COVID-19 among students, especially non-medical students, and furthermore, help to guide the efforts and plans of state health authorities for better containment of COVID-19.